PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 5 PALEMBANG - Dewi Ayu Agustina (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2014)
This study aims to produce computer-based learning media in the form of Compact Disc (CD) of learning that is valid and practical on economic subjects and know the effectiveness of computer-based learning media on economic subjects in improving student learning outcomes. The subjects of this study were randomly assigned to obtain a class X.6 of 31 students as a product trial class. Techniques of collecting data using tests, interviews, and documentation. The test is used to obtain data in the form of student learning outcomes oneconomic subjects. Interviews were conducted to obtain more detailed and clear data about the practicality of the implementation of computer-based learning, while documentation aims to obtain a picture of the implementation of computer-based learning. The test data was obtained from the test result after post test given by the teacher at the third meeting of the research. Interview data is obtained from interview result at last meeting, while documentation data obtained from validator validation result to all aspects of assessment presented in validation sheet. The test data is interpreted with KKM value ≥ 70. So that students who are declared complete 100% and declared effective. Interview data are analyzed descriptively qualitative in which students can operate the Compact Disc (CD) of learning easily and stated practically. While the documentation data obtained R = 84.83 and pertained valid.